(untitled) (Bulletin KNOB, 1989)
Although the exterior of the Townhall at Dordrecht looks like a neoclassicist building of the 19th century, behind the facade one can find the masonry of a large medieval trade center. This old Clothhall has been built between 1383 and 1387/88 for the Flemish tradesmen, who moved to the City of Dordrecht. The situation of this building, erected on the water, represents a remarkable and even unique aspect for Holland. One can suppose, that already at the end of the 14th century the space in the interior of the town was not sufficient anymore for the need of large and representative buildings. In 1544 the Clothhall obtained her new destination and became Townhall; a little bell tower was built on the roof and at the same time important changes took place in the interior. Still, the Townhall got her present appearance in the 19th century. The building was in such a bad state during the first decades of the century, that a renovation of all the facades was necessary. The old Townhall was modernised from 1835-45, however, the wooden, the hall and the roof remained as a fine example of medieval craftsmanship and can be admired again since the recent restoration.